PENGARUH PERSEDIAAN BAHAN BAKU TERHADAP LABA BERSIH PERUSAHAAN PADA PT. YOKOGAWA INDONESIA JAKARTA - Sri Setiawati; Minar Hana (POLITEKNIK LP3I JAKARTA, 2021)
This study aims to determine the effect of raw material inventory on the company's net profit at PT. Yokogawa Indonesia by using the value of Inventory-Work in Progress. The sample company financial statements for the 3 year period 2011-2013 are the data presented. quantitative methods with classical assumption testing, as well as statistical analysis, namely simple linear regression analysis using SPSS version 20 program is a stage of the research methodology. raw material inventory as variable X (independent variable) and net income as variable Y (dependent variable), with a total sample of 36 data for three years. H0 is accepted where the raw material inventory has no significant effect on net income.Keywords: Raw Material Inventory, Net Profit, Inventory Work in Progress